Asset Forfeiture Bill as a Challenge to Non-Conviction Based Asset Forfeiture - M. Rizal Bagaskoro; Irda Nur Khumaeroh; Agus Prasetia Wiranto (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Asset confiscation without criminal punishment in civil forfeiture recognizes the principle of Non Conviction Based Asset Forfeiture (NCBAF) which is a civil law instrument to confiscate assets/proceeds without going through criminal prosecution. The purpose of this writing is to design the mechanism and challenges of implementing NCBAF in the Asset Confiscation Bill. The research method used is normative juridical which emphasizes document studies or library research. The design of the PAS Bill mechanism in highlighting the traces of suspected assets is divided into several stages of practice that have been included in its content, namely starting from the tracing stage, blocking and confiscation, filing and submitting an application for asset confiscation, summons, examination in court, and asset management. The challenges of implementing NCBAF in the PAS Bill are the long process, the type which is an additional optional criminal offense, and the existence of a paradigm that pits NCBAF against the principle of the presumption of innocence so that they argue that NCBAF is contrary to Human Rights.